Euphemism types in the Washington Times online political articles: a study of semantic change - Jaganegara, Haidar; Arvian, Elsan; Noryatin, Yeni (LADU: Journal of Languages and Education, 2020)
Background: Â There is a situation when people are discussing topics that are considered sensitive which labeled vulgar or inconsiderate such as death, religion, sex, racial issues, or politics, the use of euphemism is very useful. By using the euphemism, it can turn unmentionable words into mentionable and less offensive. Turning the unmentionable or bad words into mentionable or good words that make euphemism give rise to semantic change through changing the sense of words.Purpose: The aim of this research is to find the types of euphemism in The Washington Times online political articles.Design and methods: This research applied a descriptive qualitative method, while the data were collected by close reading and observing the words, phrases, or clauses that contain the euphemism types in The Washington Times online political articles. This research applies the theory of Allan and Burridge for euphemism typesResults: As the results of representative data, the types of euphemism found in the articles are 3 metaphors, 1 remodeling, 9 circumlocutions, 1 abbreviation, 2 one-for-one substitutions, and 1 hyperbole. All of the euphemism types in this research are often used as substitute expressions in order to have a positive connotation and to save the readers from unpleasant topics or issues.